Primary Renal Synovial Sarcoma - Mehmet Gulum; Ercan Yeni; Murat Savas; Ilyas Ozardali; Ismail Ozdemir; Dilek Mil; Adem Altunkol; Halil Ciftci (Case Reports in Urology)
Synovial sarcomas are generally deep-seated tumors that most often occur in the proximity of large joints of adolescents and young adults. We describe two cases of primary renal synovial sarcoma that were treated successfully by radical nephrectomy. Synovial sarcoma originating from the kidney is extremely rare and the histogenesis is uncertain. Surgical resection and ifosfamide based chemotherapy are the mainstay for the management of renal synovial sarcoma. Fewer than 40 patients have been described in the English literature. Physicians should be aware of the possibility of malignancy in cystic renal masses and raise the suspicion of synovial sarcoma, especially when patients with renal masses are a young adult.